Role of different planting techniques in improving the water logging tolerance and productivity of sesame (Sesamum indicum L.) - Aslam, M; Nasrullah, HM; Akhtar, M; Ali, B; Akram, M; Nawaz, H; Javeed, HMR (Bangladesh Journal of Scientific and Industrial Research, 2015)
Sesame is a well known oil seed crop in arid and semiarid region of Pakistan and its productivity is affected due to sensitiveness to water logging in the root zones. The experiment was conducted at research area of Agronomic Research Station, Bahawalpur during the year 2010 and 2011. The crop was sown by three different planting techniques i.e. flat sowing with 45cm apart rows, ridge sowing with 45cm apart, bed sowing with 60/30 cm i.e. 60 cm wide beds with 30 cm furrow between the beds. The data revealed that maximum number of plants wilted in flat planting as compared to other methods of planting were taken in this experiment. It was also recorded that bed planting at 90cm apart beds gave maximum grain yield of 843 kg ha-1 followed by ridge planting (seed spreading by broadcast and with augmented furrows) with a grain yield of 811 kg ha-1. The lowest yield was obtained from conventional method of sowing which gave 349 kg ha-1 grain yield. Water logging stress in the root zone can successfully be avoided by planting sesame on beds or ridges under climatic conditions of Bahawalpur. Bangladesh J. Sci. Ind. Res. 50(3), 193-198, 2015